Estimation of the mixtures of GLMs with covariate-dependent mixing proportions. Issue 24 (16th December 2016) - Wu, Xing; Yu, Conglian
ABSTRACT: In this article, we study the estimation for a class of semiparametric mixtures of generalized linear models where mixing proportions depend on a covariate non parametrically. We investigate a backfitting estimation procedure and show the asymptotic normality of the proposed estimators under mild conditions. We conduct simulation to show the good performance of our methodology and give a real data analysis as an illustration.